90.6k views
2 votes
Which of the following expressions is not equal to 1? explain your reasoning!

Which of the following expressions is not equal to 1? explain your reasoning!-example-1

1 Answer

3 votes

Let's simplify each expression shown in the exercise:

Option a

Given:


x^3\cdot x^(-3)

You can apply the Product of powers property. This states the following:


b^n\cdot b^m=b^((n+m))

Where "b" is the base and "n" and "m" are exponents.

Then, you get:


x^3\cdot x^(-3)=x^((3+(-3)))=x^((3-3))=x^0

By definition:


b^0=1

Therefore:


x^0=1

The expression given in Option a is equal to 1.

Option b

Knowing that any number or expression with exponent zero is equal to 1, you get that:


1001^0=1

The expression given in Option b is equal to 1.

Option c

Given:


(a^2b)/(ba^2)

You can notice that the numerator and the denominator are equal, then:


(a^2b)/(ba^2)=1

The expression given in Option c is equal to 1.

Option d

Given:


(y^2)/(y^(-2))

You can simplify it using the Quotient of powers property, which states that:


(b^m)/(b^n)=b^((m-n))

Then, you get:


y^((2-(-2)))=y^((2+2))=y^4

The expression given in Option d is not equal to 1.

The answer is: Option d.

User Thaisa
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.